Implementation of the Quota System in the Regional Assembly Elections: the Analysis of Electoral Results in the Context of Women’s Epresentation on Electoral Lists - Cichosz, Marzena; Tomczak, Łukasz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
The following article concerns selected aspects of the implementation of the quota system in elections to the regional assemblies (Sejmik wojewódzki) in Poland. This comparative analysis concerns two elections: in 2010 (before the quota system was introduced) and in 2014 (after its introduction). The key questions the authors would like to address involve the number of women represented on the electoral lists in 2010 and 2014 respectively, and the number of mandates in regional assemblies awarded to women before and after the quota system was introduced, as well as the relationship between the position on the electoral list and mandates awarded to female candidates. The authors also focus on the personnel policies of political parties. Out of all regional elections, the regional assembly elections were characterized by the highest level of party dependency. Introducing the quota system resulted in an increase in the number of women represented on electoral lists, yet it did not help increase the number of mandates awarded to female candidates. One of the reasons for this situation was the strategy adopted when the positions on the electoral lists were awarded by the parties with the largest political support. The representation of women on the upper positions of the electoral lists is smaller than the quota of female representatives imposed by the electoral law, and the larger number of women on the positions further below on the electoral lists translates into smaller chances of these candidates gaining a mandate. The source data for this research analysis comes from the National Electoral Commission.

Artykuł dotyczy wybranych aspektów realizacji systemu kwotowego w wyborach do sejmików województw w Polsce. Analizą porównawczą objęte zostały dwie elekcje w 2010 (przed wprowadzeniem systemu kwotowego) i 2014 r. (po wprowadzeniu). Zasadnicze pytania, na które autorzy poszukują odpowiedzi dotyczą liczby kobiet reprezentowanych na listach wyborczych komitetów wyborczych w 2010 r. i 2014 r. oraz liczby mandatów w sejmikach województw zdobytych przez kobiety przed i po wprowadzeniu systemu kwotowego, a także zależności między miejscem na liście a uzyskaniem mandatu przez kobiety. Zwrócono uwagę na strategie kadrowe partii politycznych. Wybory do sejmików województw charakteryzowały się największym stopniem upartyjnienia wśród wszystkich rodzajów wyborów samorządowych. Wprowadzenie systemu kwotowego spowodowało wzrost liczby kobiet na listach wyborczych, ale nie wpłynęło na wzrost liczby mandatów uzyskiwanych przez kobiety. Jedną z przyczyn takiej sytuacji mogły być strategie obsadzania miejsc na listach wyborczych przez największe pod względem uzy-skanego poparcia partie polityczne. Mniejsza, od przyjętej w prawie wyborczym kwoty, reprezentacja kobiet na pierwszych miejscach list wyborczych i nadreprezentacja kobiet na miejscach dalszych, dających mniejsze szanse na zdobycie mandatu. Bazę źródłową wykorzystaną w trakcie badań stanowiły dane udostępniane przez Państwową Komisję Wyborczą.
Wdrażanie systemu kwot w wyborach do Zgromadzenia Regionalnego: analiza wyników wyborów w kontekście reprezentacji kobiet na listach wyborczych
Keywords: women; quota system; elections; regional assemblies; political parties; kobiety; system kwotowy; wybory; sejmiki województw; partie polityczne